Identifying differential survival, photolocomotor behavior, and gene expression responses to cylindrospermopsin in Danio rerio and Pimephales promelas - Scarlett, Kendall R.; Langan, Laura M.; Lovin, Lea M.; Henke, Abigail N.; Kim, Sujin; Stroski, Kevin M.; Chambliss, C. Kevin; Chatterjee, Saurabh; Scott, J. Thad; Brooks, Bryan W. (The Science of the total environment, 2025)
The global detection and impact of cylindrospermopsin (CYN), a cyanotoxin produced by several freshwater cyanobacteria, has increased in recent decades. CYN, a reported hepatotoxin, has become the subject of increasing concern due to linkages to human and wildlife poisonings, adversely affecting human health, agricultural animals, and the environment. However, it remains relatively understudied compared to other cyanotoxins despite its increasing prevalence and limited toxicological information. To begin to address this gap in knowledge, common biomedical and environmental fish models, the zebrafish and fathead minnow, respectively, were employed to examine influences of environmentally relevant CYN levels on sublethal gene transcription and behavioral responses. Though zebrafish locomotor profiles were not consistently affected by CYN, fathead minnow behaviors were altered during light conditions at the fastest swimming speed (>20 mm/s) for the three highest treatment levels (119, 677, and 1444 μg/L). Similarly, gene expression of zebrafish was only significantly upregulated for shha, a gene associated with neurotoxicity, while fathead minnow genes related to neurogenesis (shha and elav13), neurotransmitter secretion and synaptogenesis (syn2a), oxidative stress (nrf2a, gclc, sod1, gpx1a), DNA damage (fabp10a), and hepatotoxicity (cyp3a126) were significantly upregulated. This study identifies species specific sensitivities and highlights the need for future comparative studies to understand adverse outcomes resulting from CYN exposure. [Display omitted] •Cylindrospermopsin (CYN) presents water quality risks to public health and ecosystems.•Harmful cyanobacteria blooms can produce CYN, but aquatic hazards are understudied.•We employed standard designs with two fish models and verified CYN treatment levels.•CYN caused differential survival, behavior and gene expression responses between fish.•Our findings can inform future environment and health research and practice efforts.